2016
DOI: 10.15253/2175-6783.2016000500006
|View full text |Cite
|
Sign up to set email alerts
|

The effect Mat Pilates practice on muscle mass in elderly women

Abstract: Objective: to verify that the Mat Pilates practice increases muscle mass in elderly women. Methods: quasiexperimental study with primary data collection and with a convenience sample. The muscle mass of 43 elderly was evaluated for 11 weeks, by calculating the arm muscle area, before and after the intervention. Results: statistically significant difference was observed (p<0.002) between the average value of the arm muscle area, before (35.56cm 2) and after the exercises (42.72cm 2). Conclusion: mat Pilates pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…On the other hand, since the increase in ICW shows a positive correlation with muscle mass [42], as a result of checking the SMM in this study, it was found that all groups significantly increased muscle mass after exercise compared to before (CON group: SMM: z = −2.371, p = 0.018, PE group: SMM: z = −2.670, p = 0.008; Table 2), which is thought to be due to the increase in SMM as part of the weight gain. In the difference in the amount of change in SMM, the PE group showed a significant increase compared to the CON group, and the results were consistent with previous studies that reported an increase in skeletal muscle after Pilates exercise [43,44]. In addition, the same result was obtained by a study showing that the group who did Pilates exercise for 8 weeks for pregnant women increased grip strength [45] and that symptoms of urinary incontinence, which are common in pregnant women, were more effectively reduced in the Pilates exercise group than in Kegel exercise one [46].…”
Section: Effect Of Pilates On Body Compositions and Lipid Profilessupporting
confidence: 91%
“…On the other hand, since the increase in ICW shows a positive correlation with muscle mass [42], as a result of checking the SMM in this study, it was found that all groups significantly increased muscle mass after exercise compared to before (CON group: SMM: z = −2.371, p = 0.018, PE group: SMM: z = −2.670, p = 0.008; Table 2), which is thought to be due to the increase in SMM as part of the weight gain. In the difference in the amount of change in SMM, the PE group showed a significant increase compared to the CON group, and the results were consistent with previous studies that reported an increase in skeletal muscle after Pilates exercise [43,44]. In addition, the same result was obtained by a study showing that the group who did Pilates exercise for 8 weeks for pregnant women increased grip strength [45] and that symptoms of urinary incontinence, which are common in pregnant women, were more effectively reduced in the Pilates exercise group than in Kegel exercise one [46].…”
Section: Effect Of Pilates On Body Compositions and Lipid Profilessupporting
confidence: 91%
“…Contrastingly, mat Pilates resulted in significantly higher values for muscle strength. In essence, the mat Pilates method does not primarily aim to induce hypertrophy, a characteristic observed in other methods utilizing load to recruit and increase muscle fiber volume [ 47 ]. The method is characterized as a complement to hypertrophy’s role in augmenting muscle mass, with mat Pilates exercises emphasizing the quality of movement over the quantity of repetitions performed [ 22 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Queiroz, et al, 29 which evaluated the muscle mass of 43 elderly women with an average age of 73 years for 11 weeks, showed that 43 sessions of mat pilates, with a gradual increase in intensity, were sufficient to generate a positive effect on the increase of muscle mass in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Results related to increased strength and muscle mass were also verified in other investigations that used mat pilates exercises. 26,28,29,30 This modality can significantly increase people's muscle mass and strength, as calisthenics are used when performing of the exercises, that is, the body weight itself serves as resistance when performing them. 28,30 Costa, et al 17 , aimed to evaluate the quality of life of elderly women who practice and do not practice the Pilates method.…”
Section: Discussionmentioning
confidence: 99%